"Os negros cabindas, os mais inteligentes e os mais bonitos": uma análise comparativo-tematológica entre provérbios de Carolina Maria de Jesus e provérbios da filosofia tradicional de Cabinda - Vieira-Machado, Leonardo Lúcio (2023)
The thesis “'The black Cabindas, the most intelligent and the most beautiful': a comparative-thematological analysis between Proverbs by Carolina Maria de Jesus and proverbs from the traditional philosophy from Cabinda” rescues the book Proverbs (undated), the fourth and last publication in the lifetime of the Brazilian writer Carolina Maria de Jesus, and compares its content with the proverbs from that region recorded by the Spiritan priest José Martins Vaz (1970a). The main objective of this investigation was to analyse the different voices that intertwine, overlap and become entangled in these literary constructions, exploring their interests, cultural expressions and reflections of the social thematic complexes present in each context. As a methodology, we resorted to Thematology, an area of Comparative Literature from the perspective of Brunel et al. (2012), and Paremiology, a discipline focused on the study of proverbs, with emphasis on the International Type System of Proverbs by Matti Kuusi, according to Lauhakangas (2001). As a result, we discovered that of the 639 Carolinian sayings, 490 (or 76.7% of her work) are distributed across the following themes: “D. The world and human life” (97), “F. Concepts of morality” (97), “H. Social interaction” (87), “K. Social position” (87), “M. Coping and learning” (68) and “C. Basic observations and sociologic” (54), with his favouritism for the topic of the Thematic Subgroup “F1a. Ethical criteria of good and evil”, with 29 proverbs (4.5% of the work). Paired, the Main Themes of the proverbs of the author from Minas Gerais and those from West Africa are 52.6% equivalent. When compared to themes, while the interest of Carolina's proverbs is for issues of personal reflection and motivation for cooperation, from a more philosophical perspective, Cabinda's interest is for more practical and resolving issues based on everyday situations. Of the cultural expressions, the Brazilian writer resorts to the most speculative and subjective locutions (e.g.: “swamp water”, “Hitler [...] minister of death”), while in African territory manual work and culinary items make up the stylistic (“chopping firewood”, “muamba”). Reflecting the social thematic complexes, the conditions of inequality and the government's absence in social welfare policies are a constant in Carolina's proverbs, while the collection from Cabinda emphasizes the need for obedience to authorities and tradition. Based on the theoretical references and debaters of the Thematic Complex, we consider the hypothesis of political-religious bias in the paremies collected by Vaz (1970a), focused on a socio-historical ancestry under ethnographic pretext, to the detriment of the events of the collection period: anti-colonial movements throughout Africa, especially in the then overseas province against the Salazar regime. We hope that this research contributes not only to other angles of observation on Carolina's proverbial writing, and by extension on Cabinda, but also that it marks the author's place on the national and global map of paremiological studies.